The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2147/rrtm.s137829
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the leukocyte and cytokine profiles between placental and maternal circulation in pregnancy-associated malaria

Abstract: BackgroundActivation of immune cells by malaria infection induces the secretion of cytokines and the synthesis of other inflammatory mediators. This study compared the cytokine levels and leukocyte count between malaria-infected peripheral and placental blood of pregnant women before delivery and postpartum. The cytokines assessed include interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α), interleukin-4 (IL-4), interleukin-6 (IL-6) and interleukin-10 (IL-10).Materials and methodsThe subjects compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
2
11
2
Order By: Relevance
“…Moreover, the maternal peripheral level of IL-17A and the placental and neonate IFN-γ levels were not signi cantly different due to the infection. Several previous studies have shown elevated levels of type 2 anti-in ammatory cytokines IL-10 and IL-4 in the malariainfected group [13,15,23,25,30,31]. Our ndings were different from those reported by Bayoumi et al [11] and Chêne and et al [12] who found higher levels of IL-4 and IL-10 in the non-infected group.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the maternal peripheral level of IL-17A and the placental and neonate IFN-γ levels were not signi cantly different due to the infection. Several previous studies have shown elevated levels of type 2 anti-in ammatory cytokines IL-10 and IL-4 in the malariainfected group [13,15,23,25,30,31]. Our ndings were different from those reported by Bayoumi et al [11] and Chêne and et al [12] who found higher levels of IL-4 and IL-10 in the non-infected group.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the maternal peripheral level of IL-17A and the placental and neonate IFN-γ levels were not signi cantly different due to the infection. Several previous studies have shown elevated levels of type 2 anti-in ammatory cytokines IL-10 and IL-4 in the malariainfected group [12,13,15,23,25,30,31]. Conversely, the present results were different from the previous ndings in an area with unusable malaria transmission in Sudan, where higher levels of IL-4 and IL-10 in the non-infected group was reported [11].…”
Section: Discussioncontrasting
confidence: 99%
“…Findings of this study showed that IFNγ, TNFα, IL-4, IL-6 and IL-10 were elevated in infected placentas as opposed to that of uninfected placentas. This finding is in consonance with studies by (Sharma and Shukla, 2017;Okamgba et al, 2018;Lima et al, 2019) who observed that IFNγ and TNFα were increased in the parasite infected than the uninfected placenta. On the contrary, it did not agree with the finding of Bayoumi et al (2009) who observed that IFNγ, IL-4 and IL-10 were elevated in uninfected than infected placentas and Yasnot et al (2013) who observed that IL-6 and IL-10 were decreased in the infected than the uninfected placenta.…”
Section: Discussionsupporting
confidence: 92%